The Influence of Digital Leadership and Reward Systems in a Digital Work Environment on Job Engagement and Its Implications on Employee Performance in PT X's Work Unit in the Bandung Region - Inden komariah; Asti Nur Aryanti; Gurawan Dayona Ismail (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of Digital Leadership and Reward Systems in a digital work environment on Job Engagement and their implications for employee performance at PT X Regional Office Bandung. The study employed a quantitative approach using a survey method and an explanatory research design. The research population consisted of 120 active employees, all of whom were included as respondents through a saturated sampling technique. Data were collected using a questionnaire with a five-point Likert scale, while data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The findings indicate that Digital Leadership has a positive and significant effect on Job Engagement (β = 0.446; p = 0.000) and employee performance (β = 0.227; p = 0.022). The Reward System also has a positive and significant effect on Job Engagement (β = 0.356; p = 0.000), but it does not have a direct effect on employee performance (β = 0.081; p = 0.342). Furthermore, Job Engagement was found to have a positive and significant effect on employee performance (β = 0.448; p = 0.000) and emerged as the strongest predictor in the research model. The mediation analysis revealed that Job Engagement partially mediates the effect of Digital Leadership on employee performance and fully mediates the effect of the Reward System on employee performance. The research model explains 41.3% of the variance in Job Engagement and 38.8% of the variance in employee performance and demonstrates good predictive relevance. These findings emphasize the importance of strengthening digital leadership and managing reward systems oriented toward enhancing work engagement to support employee performance in the era of digital transformation.